Substitution of ice by a curing salt solution during meat batter production using the vane pump-grinder technology. (May 2016) - Irmscher, Stefan B.; Terjung, Eva-Maria; Gibis, Monika; Herrmann, Kurt; Kohlus, Reinhard; Weiss, Jochen
Abstract: Extending vane pump-grinder systems by attaching a high-shear homogenizer enables the production of finely emulsified meat batters. The integration of an injection nozzle between grinder and high-shear homogenizer allows for a curing salt solution to be injected during meat emulsion production. In this study, we examined the effects of substituting crushed ice by a curing salt solution. We postulated that the injection of a salt solution instead of the addition of ice decreases the energy consumption of the size reduction units, since forces required to comminute the raw material mixture may decrease. To this purpose, the amount of crushed ice in the meat emulsion formulation was gradually substituted by a curing salt solution injected via the nozzle. Results show that the complete substitution of ice by injection of curing salt solution did not alter the product qualities, but that substantial energy savings of up to 25% during the production of finely dispersed meat emulsions were achieved. Specifically, the power consumption of the high-shear homogenizer decreased by up to 27%. Results should be of interest to meat product manufacturers looking for new approaches to reduce costs. Highlights: Complete substitution of ice by injection of curing salt solution was feasible. Lower torques may decrease maintenance requirements of the production system. Power consumption of the high-shear homogenizer decreased by 5.3 kW. Product characteristics were only minorly influenced by the ice substitution.